Low‐dose radiotherapy in diffuse large B‐cell lymphoma. Issue 4 (25th October 2016) - Furlan, Carlo; Canzonieri, Vincenzo; Spina, Michele; Michieli, Mariagrazia; Ermacora, Anna; Maestro, Roberta; Piccinin, Sara; Bomben, Riccardo; Dal Bo, Michele; Trovo, Marco; Gattei, Valter; Tirelli, Umberto; et al.
Abstract: Low‐dose radiotherapy (LDRT) given in 2 × 2 Gy is a highly effective and safe treatment for palliation of indolent lymphomas. Otherwise, very little regarding the use of LDRT for diffuse large B‐cell lymphoma (DLBCL) has been investigated. We designed a phase 2 trial of LDRT in patients with DLBCL with indication for palliative radiation. Low‐dose radiotherapy was administered on symptomatic areas only. Clinical response was assessed 21 days after LDRT and defined as reduction >50% of maximum diameter of the radiated lesions. Quality of life was scored by the European Organisation for Research and Treatment of Cancer QLQ‐C30 questionnaire. Tumor subtype (germinal center B‐cell type versus activated B‐cell type) and the presence of TP53 mutations in pathologic specimens of the target lesion were also evaluated. Twenty‐three of twenty‐five radiated patients were evaluable for response, and 2 died of disease before the visit at 21 days. The overall response rate was 70% (16 of 23 patients), with 7 complete responses and 9 partial responses (mean duration of response, 6 months; range, 1‐39 months). Fifteen patients answered to the QLQ‐C30 questionnaires, and an improved quality of life was documented in 9 cases. TP53 mutations were detected in 2 of 6 (33%) nonresponders and in none of the responders ( P = .12). Germinal center B‐cell type responded better than activated B‐cell type (response rate was 83% and 29%, respectively, P = .01). These findings indicate that LDRT is effective for palliation in patients with DLBCL.